Antibody-mediated leucocyte cytotoxicity to Chang human liver cells in rheumatoid arthritis and other diseases. Issue 1 (February 1976) - Panayi, G S
Abstract : The incidence of an IgG-antibody which induces lymphocyte cytotoxicity to Chang human liver cells in culture was estimated in the sera of patients with rheumatoid arthritis, systemic lupus erythematosus, ankylosing spondylitis, psoriatic arthritis, Crohn's disease, ulcerative colitis, and in healthy controls. It was found in 4.1% of control subjects and in 31% of patients with rheumatoid arthritis. None of the other patient groups differed from the control group. This may be the first demonstration of an antibody response to an antigen or antigens which is almost entirely confined to patients with rheumatoid arthritis. The possibility that an antigenic similarity exists between the rheumatoid synovial membrane and Chang cells is currently under investigation.